2016
DOI: 10.5194/acp-16-541-2016
|View full text |Cite
|
Sign up to set email alerts
|

The tropopause inversion layer in baroclinic life-cycle experiments: the role of diabatic processes

Abstract: Abstract. Recent studies on the formation of a quasipermanent layer of enhanced static stability above the thermal tropopause revealed the contributions of dynamical and radiative processes. Dry dynamics leads to the evolution of a tropopause inversion layer (TIL), which is, however, too weak compared to observations and thus diabatic contributions are required. In this study we aim to assess the importance of diabatic processes in the understanding of TIL formation at midlatitudes. The non-hydrostatic model C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(83 citation statements)
references
References 37 publications
8
75
0
Order By: Relevance
“…Regarding radiation, recent modeling studies highlighted the importance of including diabatic processes related to water vapor and clouds, apart from dynamics, in order to explain the midlatitude TIL (Ferreira et al, 2016;Kunkel et al, 2016). Particularly, the baroclinic life cycle experiments by Kunkel et al (2016) that included diabatic effects from water vapor and clouds showed a faster deepening of the wave and strengthening of the TIL, along with an increase in the crosstropopause gradient of water vapor which would in turn increase radiative cooling of the tropopause.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding radiation, recent modeling studies highlighted the importance of including diabatic processes related to water vapor and clouds, apart from dynamics, in order to explain the midlatitude TIL (Ferreira et al, 2016;Kunkel et al, 2016). Particularly, the baroclinic life cycle experiments by Kunkel et al (2016) that included diabatic effects from water vapor and clouds showed a faster deepening of the wave and strengthening of the TIL, along with an increase in the crosstropopause gradient of water vapor which would in turn increase radiative cooling of the tropopause.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the baroclinic life cycle experiments by Kunkel et al (2016) that included diabatic effects from water vapor and clouds showed a faster deepening of the wave and strengthening of the TIL, along with an increase in the crosstropopause gradient of water vapor which would in turn increase radiative cooling of the tropopause.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chagnon et al () also argued that the transport of moisture by the WCB would enhance the effects of long‐wave radiation. Kunkel et al () showed similar results for the TIL: long‐wave radiation strengthened the TIL and transport of moisture to the tropopause results in a more rapid formation of the TIL. However, these results are limited to case studies (Chagnon & Gray, ; Chagnon et al, ) and idealized simulations (Kunkel et al, ).…”
Section: Processes Affecting Tropopause Sharpnessmentioning
confidence: 99%